에너지 저감을 위한 사용자 및 위치인식 기술 적용 디밍 조명제어 시스템 연구 - 최기현(Kihyun Choi); 김용성(Yongseong Kim); 이행우(Henagwoo Lee); 서장후(Janghoo Seo) (설비공학 논문집, 27(1), 2015)
Although research and technology developments have recently increased to save lighting energy within buildings, such research and technology development are judged to be unsuitable for energy savings since they are limited in the sense that the application of the technology is fragmented. This study proposes a user and location awareness technology applied to dimming lighting control system and verified the effectiveness of energy savings by building a test bed. The results were as follows : 1) This study suggested a user and location awareness technology applied to dimming lighting control system. 2) The system shows 96.6% and 82.8% energy saving rates, respectively, on the basis of one user, compared to an on/off lighting control and the user and location awareness technology applied to on/off lighting control system. 3) The energy consumption of the user and location awareness technology applied to on/off lighting control system and the user and location awareness technology applied to dimming lighting control system increased to 96.6%, 88.3%, and 59.6% and 82.8%, 85.0%, 51.5%, respectively, on the basis of one, two, and three users, compared to the on/off lighting control system. This study confirmed the energy saving performance of the user and location awareness technology applied to the dimming lighting control system through performance evaluation. In this regard, further study needs to be undertaken to evaluate the performance at night time.